Up-regulation of CTRP12 ameliorates hypoxia/re-oxygenation-induced cardiomyocyte injury by inhibiting apoptosis, oxidative stress, and inflammation via the enhancement of Nrf2 signaling. (December 2021) - Jin, Ai-Ping; Zhang, Qian-Rong; Yang, Cui-Ling; Ye, Sha; Cheng, Hai-Juan; Zheng, Yuan-Yuan
C1q/TNF-related protein 12 (CTRP12) has been reported to play a key role in coronary artery disease. However, whether CTRP12 plays a role in the regulation of myocardial ischemia-reperfusion injury is not fully understood. The goals of this work were to assess the possible relationship between CTRP12 and myocardial ischemia-reperfusion injury. Here, we exposed cardiomyocytes to hypoxia/re-oxygenation (H/R) to establish an in vitro cardiomyocyte injury model of myocardial ischemia-reperfusion injury. Our results showed that H/R treatment resulted in a decrease in CTRP12 expression in cardiomyocytes. The up-regulation of CTRP12 ameliorated H/R-induced cardiomyocyte injury via the down-regulation of apoptosis, oxidative stress, and inflammation. In contrast, the knockdown of CTRP12 enhanced cardiomyocyte sensitivity to H/R-induced cardiomyocyte injury. Further investigation showed that CTRP12 enhanced the levels of nuclear Nrf2 and increased the expression of Nrf2 target genes in cardiomyocytes exposed to H/R. However, the inhibition of Nrf2 markedly diminished CTRP12-overexpression-mediated cardioprotective effects against H/R injury. Overall, these data indicate that CTRP12 protects against H/R-induced cardiomyocyte injury by inhibiting apoptosis, oxidative stress, and inflammation via the enhancement of Nrf2 signaling. This work suggests a potential role of CTRP12 in myocardial ischemia-reperfusion injury and proposes it as an attractive target for cardioprotection.